Toward a Socially Responsible Psychology for a Global Era - Mustakova-Possardt, Elena (International and Cultural Psychology, 2014)
The progression is a logical one: in keeping with an era noted for advances toward greater equality and an irreversible trend toward globalization--but also marked with bigotry, persecution, and environmental destruction-- psychology has developed the potential to heal large populations as well as individuals. Toward a Socially Responsible Psychology for a Global Era describes the changes necessary to address the systemic problems affecting an increasingly distressed world. This path-breaking resource challenges readers to rethink the basic and implicit assumptions of psychology, reframing the field in terms of its responsibility as a healing science and force for social justice, and elucidates the context that makes this paradigm shift so necessary. Contributors analyze not only central issues shaping the field, but a practical framework for a redefined discipline, with concepts such as socially responsible inquiry and clinical practice, and strategies for working with like-minded communities and institutions toward key objectives, among them: Achieving a sustainable future. Developing clinical practice suited to a global community. Attaining global consciousness in the context of societal health. Overcoming racism, sexism, and poverty. Healing the causes of human suffering and environmental harm. Conceptualizing and actualizing justice restoratively. Achieving a psychology of nonviolence. A volume with a clear moral vision, Toward a Socially Responsible Psychology for a Global Era is an affirmation of purpose and a call to action for psychologists to bring greater relevance to their profession towards building a shared just, humane and sustainable future